Techno-economic feasibility assessment of CO2 capture from coal-fired power plants using molecularly imprinted polymer - Dataset - Hanak, Dawid P.; Manovic, Vasilije (Cranfield University, 2017)
A dataset for the article 'Techno-economic analysis feasibility assessment of CO2 capture from coal-fired power plants using molecularly imprinted polymer'.
Keywords: 'Thermodynamics analyses'; 'Economic Assessment'; 'Carbon Capture Systems'; 'Carbon Capture Engineering (excl. Sequestration)'; 'Chemical Engineering Design'; 'Energy Generation; Conversion and Storage Engineering'; 'Mechanical Engineering'